Controlling photonic spin Hall effect in graphene-dielectric structure by optical pumping. (6th November 2020) - Dong, Peng; Cheng, Jie; Da, Haixia; Yan, Xiaohong
Abstract: The photonic spin Hall effect (SHE) provides an effective way to manipulate the spin-polarized photons. However, the spin-dependent splitting is very tiny due to the weak spin–orbit coupling, and previous investigations for enhancing this phenomenon have some serious limitations (e.g. inconvenient to tune, inadequate attention in terahertz region). Therefore, controlling and enhancing the photonic SHE in a flexible way is highly desirable, especially for terahertz region. In this contribution, we propose a method to manipulate the photonic SHE by taking advantage of tunable optical properties of graphene via weak optical pumping. We find that photonic SHE of graphene-dielectric structure in terahertz region is quite sensitive to the pumping power. The spin shift for H polarized incident beam can reach its upper limitation under the optimal pumping power, which is related to the zero value of the real part of graphene conductivity. These findings may provide a new degree of freedom for the design of tunable spin-based photonic devices in the future.